Metal-state single crystal material with ordered charges and preparation method of metal-state single crystal material

Through the "two-step method" high-voltage single crystal growth technology and high-temperature and high-pressure oxygen supplementation treatment, CaFe0.95Co0.05O3 single crystal material with charge-ordered and metallic state was successfully prepared, which solved the problem of insulator behavior of existing charge-ordered materials and achieved the combination of metallic conductivity and charge-ordered state.

CN119900084APending Publication Date: 2025-04-29INSTITUTE OF PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311411639.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Existing charged-ordered materials usually exhibit insulator behavior, limiting their widespread application, and urgently need a material with charge-ordered and metallic state.

Method used

Through the "two-step method" large-size high-pressure single crystal growth technology, firstly, oxygen-deficient CaFe0.95Co0.05O2.5 single crystal was grown, and then high-temperature and high-pressure technology was used to react with the oxidant to supplement the missing oxygen to obtain the metallic single crystal material CaFe0.95Co0.05O3 with a charge-ordered charge.

Benefits of technology

The existence of Fe3+ and Fe5+ charge order states below 75K is achieved, and the conductivity of the material is metallic, which has high scientific research value and potential application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004518443230000011
    Figure HDA0004518443230000011
  • Figure HDA0004518443230000012
    Figure HDA0004518443230000012
  • Figure HDA0004518443230000021
    Figure HDA0004518443230000021
Patent Text Reader

Abstract

The invention provides a metal-state single crystal material with ordered charges. The metal-state single crystal material has the following chemical formula of CaFe < 0.95 > Co < 0.05 > O < 3 >. The invention also provides a method for preparing the metal-state single crystal material with ordered charges, which comprises the following steps: (1) mixing CaCO3, Fe2O3 and Co3O4, and fully and uniformly grinding to obtain a mixture; (2) carrying out first roasting and first annealing on the mixture; (3) grinding the product subjected to the first annealing, and pressing into a rod-shaped object; (4) carrying out second roasting and second annealing on the rod-shaped object, so as to obtain a CaFe < 0.95 > Co < 0.05 > O < 2.5 > polycrystalline rod; (5) taking the CaFe < 0.95 > Co < 0.05 > O < 2.5 > polycrystalline rod as a material rod, and growing a CaFe < 0.95 > Co < 0.05 > O < 2.5 > single crystal through an optical floating zone method; and (6) the CaFe < 0.95 > Co < 0.05 > O < 2.5 > single crystal and an oxidizing agent are subjected to a high-temperature and high-pressure reaction, vacant oxygen is supplemented, and the metal-state single crystal material CaFe < 0.95 > Co < 0.05 > O < 3 > with ordered charges is obtained. The CaFe0. 95Co0. 05O3 single crystal material provided by the invention has a charge order state and a metal state at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of materials, and in particular, relates to a metallic single crystal material with ordered charges and a preparation method thereof. Background Art

[0002] Charge ordering refers to the accommodation of two or more different charge states at different atomic positions, resulting in significant changes in the material structure and physical properties. In transition metal oxides, such as perovskite manganese oxides, the mixed valence state of Mn is transformed into different Mn 3+ and Mn 4+ state, occupying different atomic positions, leading to the transition of crystal structure and electrical transport, and the existence of giant magnetoresistance (MR) effect, which has potential application prospects in electronic devices, so charge ordering has received widespread attention.

[0003] Usually, the charge-ordered system is electrically insulating. For example, there is CaFe 1-x Co x O3 (0≤x≤0.5) polycrystalline material (reference literature Physical properties of Co-substituted iron perovskite systems. Solid State Ionics 108 (1998) 221-226). The iron element in the CaFeO3 polycrystalline sample is in a typical charge ordered state below 290K, that is, the iron element is Fe 3+ and Fe 5+ And occupy two different positions in its lattice, and behave as an insulator in terms of conductivity. Charge-ordered materials usually exhibit a single insulator behavior, which limits their wide application. Therefore, there is an urgent need for a material with charge order and in a metallic state. Summary of the invention

[0004] The object of the present invention is to provide a single crystal material with ordered charge and in a metallic state. The material has Fe 3+ and Fe 5+ A charge-ordered state in which charges are arranged in an orderly manner in the crystal lattice, but its conductivity is that of a metallic state.

[0005] Another object of the present invention is to provide a method for preparing a metallic single crystal material with charge order.

[0006] The above-mentioned object of the present invention is achieved through the following technical solutions.

[0007] In the context of the present invention, some terms of the present invention have the following definitions:

[0008] Metallic state: The material has a low resistivity and good conductivity. There are electron or hole carriers in the material, and its resistivity usually decreases as the temperature decreases.

[0009] Insulator: A material with a high resistivity that is a poor conductor of electricity. Usually resistivity increases as temperature decreases.

[0010] Charge order: Elements of different valence states in a material are arranged regularly in the crystal lattice. Usually, the conductivity of a charge-ordered material behaves as an insulator.

[0011] Single crystal: The crystal lattice of the entire sample is continuous all the way to the edge of the sample, with no grain boundaries inside. Because there are no grain boundaries, single crystals are suitable for observing the intrinsic properties of the material, such as phenomena that cannot be observed in polycrystals.

[0012] Polycrystalline: Polycrystalline materials are a collection of many tiny grains, which are in a state of aggregation separated by interfaces. The characteristic of polycrystalline is that its various properties are determined by the properties of the grains and grain boundaries that constitute it.

[0013] Neutron diffraction: Neutron diffraction usually refers to the Bragg diffraction that occurs when neutrons (thermal neutrons) with a de Broglie wavelength of about 1 angstrom pass through crystalline materials. The neutron diffraction method is one of the important means to study the structure of matter.

[0014] Laue diffraction pattern: X-ray diffraction pattern of a single crystal. Clear spots indicate that the sample is a single crystal; if it is a ring-shaped diffraction pattern, it means that the sample is polycrystalline.

[0015] Mössbauer spectroscopy: Some radioactive nuclei in solids have a certain probability of emitting gamma rays without recoil, and the gamma photons carry all the nuclear transition energy. The same nuclei in the ground state of the solid also have a certain probability of resonantly absorbing the gamma rays emitted by the former without recoil. This phenomenon of atomic nuclei emitting or resonantly absorbing gamma rays without recoil was later called the Mössbauer effect. Mössbauer spectroscopy can be used to calibrate CaFe 0.95 Co 0.05 O 2.5 The valence state of iron element in China.

[0016] In one aspect, the present invention provides a metallic single crystal material having charge order, which has the following chemical formula: CaFe 0.95 Co 0.05 O3.

[0017] Preferably, the X-ray powder diffraction pattern of the charge-ordered metallic single crystal material described in the present invention using Cu target Kα diffraction and expressed in 2θ angles has diffraction peaks at 23.56°, 33.60°, 48.24°, 60.14°, 70.64°, and 80.55, and the 2θ angle measurement accuracy is ±0.005°.

[0018] Preferably, the lattice of the metallic single crystal material with charge order in the present invention belongs to the space group Pbnm, and the lattice constant is

[0019] Preferably, the powder XRD pattern and refined pattern of the metallic single crystal material with ordered charge of the present invention are as follows: Figure 4B shown.

[0020] Preferably, the Laue diffraction pattern of the metallic single crystal material with ordered charge according to the present invention has obvious spots, such as Figure 4A shown.

[0021] In another aspect, the present invention provides a method for preparing the metallic single crystal material having charge order of the present invention, comprising the following steps:

[0022] (1) mixing CaCO3, Fe2O3, and Co3O4 and grinding them uniformly to obtain a mixture;

[0023] (2) subjecting the mixture to a first calcination and a first annealing;

[0024] (3) grinding the product after the first annealing and pressing it into a rod-shaped object;

[0025] (4) The rod-shaped material is subjected to a second calcination and a second annealing to obtain CaFe 0.95 Co 0.05 O 2.5 polycrystalline rod;

[0026] (5) With the CaFe 0.95 Co 0.05 O 2.5 The polycrystalline rod is used as the material rod, and CaFe is grown by the optical floating zone method. 0.95 Co 0.05 O 2.5 Single crystal;

[0027] (6) CaFe 0.95 Co 0.05 O 2.5 The single crystal reacts with an oxidant under high temperature and high pressure to supplement the missing oxygen to obtain a metallic single crystal material CaFe with ordered charge. 0.95 Co 0.05 O3.

[0028] The present invention synthesizes CaFe 0.95 Co 0.05 O3 single crystals are grown using a two-step large-size high-pressure single crystal growth technology. First, oxygen-deficient CaFe 0.95 Co 0.05 O 2.5 The single crystal is then treated with an oxidant at high temperature and high pressure to replenish the missing oxygen. This method can obtain a large-size high-pressure single crystal such as 4mm (see the invention Figure 3 It should be noted that the method of the present invention can also prepare single crystals of larger sizes, not just the 4 mm presented in the present invention. The specific size of the prepared single crystal depends mainly on the cavity and precursor single crystal (such as the CaFe 0.95 Co 0.05 O 2.5 How big is a single crystal?

[0029] Preferably, in the method described in the present invention, the CaCO3, Fe2O3 and Co3O4 are mixed according to the molar ratio of CaCO3:Fe2O3:Co3O4=1:0.475:0.01667.

[0030] Preferably, in the method of the present invention, the first calcination is carried out under the following conditions: the calcination temperature is 950 to 1100° C., and the calcination time is 15 to 30 hours.

[0031] Preferably, in the method of the present invention, the first annealing is performed by cooling the temperature to room temperature at a rate of 2-10° C. / min.

[0032] Preferably, in the method of the present invention, the second calcination is carried out under the following conditions: the calcination temperature is 950 to 1100° C., and the calcination time is 15 to 30 hours.

[0033] Preferably, in the method of the present invention, the second annealing is performed by cooling the temperature to room temperature at a rate of 2-10° C. / min.

[0034] Preferably, in the method of the present invention, the optical floating zone method is carried out under the following conditions: the seed crystal is CaFe 0.95 Co 0.05 O 2.5 For polycrystalline, the growth atmosphere is argon or air, and the seed rod downward speed and rotation speed are 1-3 mm / h and 15-40 r / min respectively.

[0035] Preferably, in the method described in the present invention, the oxidant is selected from one or more of KClO4, KCIO3, NaCIO4, NaCIO3 and Na2O2 powder.

[0036] Preferably, in the method of the present invention, the number of oxygen atoms provided by thermal decomposition of KClO4 powder (each molecule of KClO4 produces 4 oxygen atoms when thermally decomposed) is greater than or equal to CaFe 0.95 Co 0.05 O 2.5 The number of oxygen atoms required to complete the single crystal (per molecule of CaFe 0.95 Co 0.05 O 2.5 0.5 oxygen atoms need to be supplemented).

[0037] Preferably, in a specific embodiment of the present invention, KClO4 can provide three times the oxygen required for supplemental oxygen. For example, a molecular weight of CaFe 0.95 Co 0.05 O 2.5 to CaFe 0.95 Co 0.05 O3 needs to supplement 0.5 oxygen atoms, so KClO4 with a molecular weight of 0.375 is needed to provide 1.5 oxygen atoms, and the corresponding CaFe 0.95 Co 0.05 O 2.5 The mass ratio of single crystal to KClO4 powder is 1:0.3818.

[0038] Preferably, in the method described in the present invention, the device for high temperature and high pressure reaction is a six-sided top press or a 6-8 type two-stage push press.

[0039] Preferably, in the method described in the present invention, the high temperature and high pressure reaction is carried out under the following conditions: reaction pressure is 5 to 8 GPa, reaction temperature is 850 to 950° C., and reaction time is 15 to 40 min.

[0040] Preferably, in the method of the present invention, the oxidant is uniformly distributed in the CaFe 0.95 Co 0.05 O 2.5 The single crystal is sealed with a gold capsule.

[0041] In a specific embodiment of the present invention, the precursor CaFe 0.95 Co 0.05 O 2.5 The single crystal growth method is not limited to the optical floating zone method, and other single crystal growth methods are also possible, such as the solvent method, the pulling method, the vapor deposition method, etc.

[0042] In a specific embodiment of the present invention, the raw materials are not limited to CaCO3, Fe2O3, and Co3O4. It is only necessary to ensure that the molar ratio of the three metal elements Ca, Fe, and Co added meets 1:0.95:0.05.

[0043] The present invention has the following beneficial effects:

[0044] The CaFe provided by the present invention 0.95 Co 0.05 O3 single crystal material has both a charge-ordered state and a metallic state. This charge-ordered metallic state is not found in its polycrystalline material and is extremely rare. It has high scientific research value and potential application value.

[0045] CaFe of the present invention 0.95 Co 0.05 The O3 single crystal growth method can produce large-size (above 4mm) single crystals. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] The embodiments of the present invention are described in detail below with reference to the accompanying drawings, wherein:

[0047] Figure 1 The resistivity-temperature curve of CaFeO3 single crystal is shown in Figure 2. CD Fe 4+ →Fe 3+ +Fe 5+ Transition temperature;

[0048] Figure 2 The CaFe prepared in Example 1 of the present invention is shown 0.95 Co 0.05 O 2.5 Single crystal real photo ( Figure 2 A) Laue diffraction pattern ( Figure 2 B), and its powder XRD pattern ( Figure 2 C);

[0049] Figure 3 The CaFe obtained by high temperature and high pressure treatment in Example 1 of the present invention is shown. 0.95 Co 0.05 O3 single crystal;

[0050] Figure 4A The CaFe obtained by high temperature and high pressure treatment in Example 1 of the present invention is shown. 0.95 Co 0.05 Laue diffraction pattern of O3 single crystal;

[0051] Figure 4B The CaFe obtained by high temperature and high pressure treatment in Example 1 of the present invention is shown. 0.95 Co 0.05 Powder XRD pattern of O3 single crystal;

[0052] Figure 5 The CaFe prepared in Example 1 of the present invention is shown 0.95 Co0.05 The resistivity curve of O3 single crystal changes with temperature;

[0053] Figure 6 The CaFe prepared in Example 1 of the present invention is shown 0.95 Co 0.05 Mössbauer spectrum of O3 single crystal. The green, blue and yellow lines are Fe 3+ , Fe 5+ and Fe 4+ Spectral line fitting curve, red is green Fe 3+ and blue Fe 5+ The fitted data curve obtained by superposition;

[0054] Figure 7 The CaFe prepared in Example 1 of the present invention is shown 0.95 Co 0.05 Powder neutron diffraction pattern and refinement results of O3 single crystal at 4K; the observed value (circle), fitted value (red line) and difference (blue line) in the figure; the purple scale in the first row indicates the position of the nuclear Bragg reflection with P21 / n space group, indicating that CaFe 0.95 Co 0.05 O3 single crystal is Fe 3+ and Fe 5+ The second and third scale lines represent the reflection of the helical antiferromagnetic spin structure.

[0055] Figure 8 The CaFe prepared in Comparative Example 1 of the present invention is shown 0.95 Co 0.05 The resistivity curve of O3 polycrystalline block changes with temperature. DETAILED DESCRIPTION

[0056] The present invention is further described in detail below in conjunction with specific embodiments. The given examples are only for illustrating the present invention, rather than for limiting the scope of the present invention.

[0057] Example 1

[0058] Using the "two-step" large-size high-pressure single crystal growth method, CaFe 0.95 Co 0.05 O3 single crystal. The specific preparation steps include the following:

[0059] Step I: Growth of oxygen-deficient CaFe using optical floating zone single crystal growth technology 0.95 Co 0.05 O 2.5 Single crystal:

[0060] (I-1) About 10 g of chemical raw materials CaCO3, Fe2O3, and Co3O4 were prepared in a molar ratio of 1:0.475:0.01667, ground and mixed thoroughly in a mortar, and then placed in an alumina crucible and kept at 1000°C for 24 hours, and then annealed at 5°C / min to room temperature;

[0061] (I-2) The sample obtained in step (1) was re-ground and pressed into a rod with a diameter of about 5 mm and a length of about 10 cm using a hydraulic press; the rod was then placed in an alumina crucible again, kept at 1000° C. for 24 hours, and then annealed at 5° C. / min to room temperature to obtain high-purity CaFe 0.95 Co 0.05 O 2.5 a polycrystalline rod, which is an oxygen-deficient precursor;

[0062] (I-3) CaFe 0.95 Co 0.05 O 2.5 The polycrystalline rod is used as the material rod, and the CaFe 0.95 Co 0.05 O 2.5 Single crystal; Growth conditions: CaFe 0.95 Co 0.05 O 2.5 Polycrystalline was used as seed crystal, the growth atmosphere was Ar gas, and the seed crystal rod downward speed and rotation speed were 2mm / h and 20r / min respectively;

[0063] (I-4) The obtained CaFe was detected by Laue diffractometer 0.95 Co 0.05 O 2.5 Single crystal quality; Laue image shows clear spots.

[0064] Step II: Use high temperature and high pressure technology to treat with high temperature and high pressure under the condition of oxidant to supplement CaFe 0.95 Co 0.05 O 2.5 The missing oxygen gives CaFe 0.95 Co 0.05 O3 single crystal:

[0065] (II-1) The obtained CaFe 0.95 Co 0.05 O 2.5 The single crystal is cut into pieces with a height of about 4 mm, and the diameter is ground down to a size that can fit into the gold capsule sample cavity of the high-pressure device with sandpaper; then the piece is placed into the gold capsule together with KClO4 powder, where the mass of KClO4 is CaFe 0.95 Co 0.05 O 2.50.3818 times of the single crystal, KClO4 powder is struck with a hammer, and an equal amount is filled in CaFe 0.7 Co 0.3 O 2.5 The upper and lower ends of the single crystal block are finally sealed with a gold capsule;

[0066] (II-2) The gold capsule was subjected to high temperature and high pressure treatment using a six-sided top press, where the pressure was 6 GPa, the temperature was 800 °C, and the treatment time was 30 minutes, and finally the CaFe 0.95 Co 0.05 O3 single crystal.

[0067] Figure 2 The CaFe prepared in Example 1 of the present invention is shown 0.95 Co 0.05 O 2.5 Single crystal real photo ( Figure 2 A) Laue diffraction pattern ( Figure 2 B), and its powder XRD pattern ( Figure 2 C).

[0068] Figure 3 The CaFe obtained by high temperature and high pressure treatment in Example 1 of the present invention is shown. 0.95 Co 0.05 O3 single crystal.

[0069] Figure 4A The CaFe obtained by high temperature and high pressure treatment in Example 1 of the present invention is shown. 0.95 Co 0.05 Laue diffraction pattern of O3 single crystal.

[0070] Figure 4B The CaFe obtained by high temperature and high pressure treatment in Example 1 of the present invention is shown. 0.95 Co 0.05 Powder XRD pattern of O3 single crystal.

[0071] The precursor CaFe used for oxygen supplementation of high temperature and high pressure equipment in use according to the present invention 0.95 Co 0.05 O 2.5 is a single crystal sample (see Figure 2 A, the Laue diffraction pattern has clear spots, indicating that it is a single crystal), CaFe 0.95 Co 0.05 O3 is also a single crystal (see Figure 4A The Laue diffraction pattern has clear spots, indicating that it is a single crystal). Its powder XRD spectrum is different from the original Figure 2 C turns into Figure 4B, indicating that its structure has changed from oxygen-deficient calcium iron ore structure to ABO3 perovskite structure, and the missing oxygen has been supplemented.

[0072] The technical solution of the present invention has the advantage that the obtained product is CaFe 0.95 Co 0.05 O3 single crystal. Whether it is a single crystal is to obtain a CaFe with a charge-ordered state and a metallic state 0.95 Co 0.05 The key to O3. Figure 5 CaFe 0.95 Co 0.05 The data of the resistivity change of O3 single crystal with temperature shows that below about 75K, its resistivity decreases as the temperature decreases, and it is in a metallic state.

[0073] Figure 6 The CaFe prepared in Example 1 of the present invention is shown 0.95 Co 0.05 Mössbauer spectrum of O3 single crystal. The green, blue and yellow lines are Fe 3+ , Fe 5+ and Fe 4+ The spectral line fitting curve is shown in red, and the fitting data curve is obtained by superimposing the green and blue fitting. 57 Isotope raw materials for CaFe 0.95 Co 0.05 O3 single crystal (without changing its chemical properties), measure the Mössbauer spectrum (see Figure 6 ) found that in the low temperature range of 100K and below, the Mössbauer spectrum can be used to 3+ and Fe 5+ The spectrum is fitted in a 1:1 manner.

[0074] Furthermore, usually charge-ordered materials are insulators, such as CaFeO3 (see Figure 1 ) As the temperature decreases, a transition from metal to insulator occurs at 290K, and the space group of the lattice structure changes from orthorhombic Pbnm to monoclinic P21 / n (orthorhombic Pbnm→monoclinic P21 / n), indicating that the iron element is transformed from a single Fe 4+ The metallic state is transformed into Fe 3+ and Fe 5+ The charge-ordered insulating state is arranged in an orderly manner in the lattice. The P21 / n space group has two different Fe 3+ and Fe 5+ Position, its appearance is the key basis for judging the ordered state of charge.

[0075] Based on CaFe 0.95 Co 0.05The powder neutron diffraction of O3 single crystal after grinding into powder shows that it has a charge-ordered P21 / n crystal structure below room temperature (300K) and as low as 4K (see Figure 7 ). 0.95 Co 0.05 The iron element in O3 single crystal is Fe 3+ and Fe 5+ Therefore, the technical solution of the present invention obtains a metallic state CaFe with orderly arrangement of charges. 0.95 Co 0.05 O3 single crystal.

[0076] Comparative Example 1

[0077] Preparation of CaFe 0.95 Co 0.05 O3 polycrystalline steps:

[0078] (1) About 10 g of chemical raw materials CaCO3, Fe2O3, and Co3O4 were prepared in a molar ratio of 1:0.475:0.01667, ground and mixed thoroughly in a mortar, and then placed in an alumina crucible and kept at 1000°C for 24 hours, and then annealed at 5°C / min to room temperature;

[0079] (2) Using high temperature and high pressure technology, high temperature and high pressure treatment under the condition of oxidant to supplement CaFe 0.95 Co 0.05 O 2.5 The missing oxygen gives CaFe 0.95 Co 0.05 O3 polycrystalline:

[0080] The sample obtained in step (1) was ground again and knocked with KClO4 powder by a hammer into a gold capsule, where the mass of KClO4 is CaFe 0.95 Co 0.05 O 2.5 0.3818 times of the powder, KClO4 powder is hit with a hammer, and an equal amount is filled in the CaFe 0.7 Co 0.3 O 2.5 The upper and lower ends of the powder are snapped shut and sealed with a gold capsule;

[0081] (3) The gold capsule prepared in step (2) was subjected to high temperature and high pressure treatment using a six-sided top press, wherein the pressure was 6 GPa, the temperature was 800° C., and the treatment time was 30 minutes, and finally CaFe 0.95 Co 0.05 O3 polycrystalline.

[0082] Figure 8 The CaFe prepared in Comparative Example 1 of the present invention is shown 0.95Co 0.05 The resistivity curve of O3 polycrystalline block varies with temperature. 0.95 Co 0.05 The resistivity of O3 polycrystalline samples in the full temperature range from room temperature to 2K increases as the temperature decreases, which is an insulator behavior. 0.95 Co 0.05 O3 polycrystalline samples do not have a charge-ordered metallic state.

Claims

1. A metallic single crystal material with charge order having the following chemical formula: CaFe 0.95 Co 0.05 O3.

2. The metallic single crystal material with charge order according to claim 1, wherein: Using Cu target Kα diffraction, its X-ray powder diffraction pattern expressed in 2θ angles has diffraction peaks at 23.56°, 33.60°, 48.24°, 60.14°, 70.64°, and 80.55, and the 2θ angle measurement accuracy is ±0.005°; Preferably, the lattice of the metallic single crystal material with charge order belongs to the space group Pbnm, and the lattice constant is Preferably, the powder XRD pattern and refined image of the metallic single crystal material with charge order are shown in FIG4B .

3. The metallic single crystal material with charge order according to claim 1, wherein: The Laue diffraction pattern of the metallic single crystal material with charge order has obvious spots, as shown in FIG4A .

4. A method for preparing the metallic single crystal material with charge order according to any one of claims 1 to 3, comprising the following steps: (1) mixing CaCO3, Fe2O3, and Co3O4 and grinding them uniformly to obtain a mixture; (2) subjecting the mixture to a first calcination and a first annealing; (3) grinding the product after the first annealing and pressing it into a rod-shaped object; (4) The rod-shaped material is subjected to a second calcination and a second annealing to obtain CaFe 0.95 Co 0.05 O 2.5 polycrystalline rod; (5) With the CaFe 0.95 Co 0.05 O 2.5 The polycrystalline rod is used as the material rod, and CaFe is grown by the optical floating zone method. 0.95 Co 0.05 O 2.5 Single crystal; (6) CaFe 0.95 Co 0.05 O 2.5 The single crystal reacts with an oxidant under high temperature and high pressure to supplement the missing oxygen to obtain a metallic single crystal material CaFe with ordered charge. 0.95 Co 0.05 O3.

5. The method according to claim 4, wherein: The CaCO3, Fe2O3 and Co3O4 are mixed according to the molar ratio of CaCO3:Fe2O3:Co3O4=1:0.475:0.01667.

6. The method according to claim 4, wherein: The first calcination is carried out under the following conditions: the calcination temperature is 950 to 1100° C. and the calcination time is 15 to 30 hours; Preferably, the first annealing is performed by cooling the temperature to room temperature at a rate of 2-10° C. / min.

7. The method according to claim 4, wherein: The second calcination is carried out under the following conditions: the calcination temperature is 950 to 1100° C. and the calcination time is 15 to 30 hours; Preferably, the second annealing is performed by cooling down to room temperature at 2-10°C / min; Preferably, the optical floating zone method is carried out under the following conditions: the seed crystal is CaFe 0.95 Co 0.05 O 2.5 For polycrystalline, the growth atmosphere is argon or air, and the seed rod downward speed and rotation speed are 1.5-3 mm / h and 15-40 r / min respectively.

8. The method according to claim 4, wherein: The oxidant is selected from one or more of KCIO3, KClO4, NaCIO3, NaCIO4 and Na2O2 powder.

9. The method according to claim 8, wherein: The mass of KClO4 powder is greater than or equal to CaFe 0.95 Co 0.05 O 2.5 0.3818 times the mass of a single crystal.

10. The method according to claim 4, wherein: The device for high temperature and high pressure reaction is a six-sided top press or a 6-8 type two-stage push press; Preferably, the high temperature and high pressure reaction is carried out under the following conditions: reaction pressure is 5 to 8 GPa, reaction temperature is 800 to 950° C., and reaction time is 15 to 40 min; Preferably, the oxidant is evenly distributed in the CaFe 0.95 Co 0.05 O 2.5 The single crystal is surrounded and sealed with a gold capsule.